Digital Play in Language Learning: A Narrative-Based Approach to Understanding Student Motivation in Interactive Arabic Assessments - Desvia Rahmawati; Musli Musli; Mustar Mustar; Dina Chabib Uluum; Putri Hardiyanti; Abdul Hakim Abdurrahman Husein; Zakiyatunnisa Al Mubarokah; Mohamad Hussin (International Journal of Educational Narratives, 2026)
Background. The development of digital technology in education has encouraged teachers to implement interactive learning media to increase student engagement during the learning process. In Arabic language learning, conventional teaching methods often make students less active and less motivated during classroom activities. Quizizz is one of the gamification-based learning platforms that can create a more interactive, competitive, and enjoyable learning environment for students. Purpose. This study aimed to explore students’ learning experiences during the implementation of Quizizz in Arabic language learning, particularly related to emotional engagement, classroom participation, interaction, motivation, and reflective learning experiences. Method. This study employed a qualitative approach using Narrative Inquiry with a phenomenological-narrative orientation. The participants consisted of one Arabic language teacher and four students selected purposively based on their involvement in Quizizz-based learning activities. Data were collected through in-depth interviews, classroom observations, reflective conversations, and documentation. Data analysis was conducted using thematic narrative analysis by organizing participants’ experiences into thematic clusters. Results. The findings showed that the use of Quizizz increased students’ emotional engagement, classroom participation, interaction, motivation, and self-confidence during Arabic learning activities. Students experienced a more interactive and enjoyable learning atmosphere through leaderboard features, scoring systems, and direct feedback during quizzes. Conclusion. Quizizz not only functioned as a digital evaluation tool but also created meaningful learning experiences through interactive, reflective, and gamified learning activities in Arabic language learning.